Stability and voids properties of hot mix asphalt containing black rice husk ash - Putra Jaya, Ramadhansyah; Noram Irwan, Ramli; Mohamad Idris, Ali; Mohd Ezree, Abdullah; Siti Khatijah, A. B.; Norhidayah, Abdul Hassan; Haryati, Yaacob (IOP Publishing, 2019)
Asphalt durability is often linked to the thickness of the asphalt coating on the aggregate particles. In order to have an adequate film thickness in asphaltic concrete, there must be sufficient space between the aggregate particles in the compacted pavement. This void space is referred to as voids properties. Hence, this study investigates the performance of black rice husk ash as (BRHA) modified binder on stability and voids characteristics of hot mix asphalt. Four BRHA were used as in this study namely 0%, 2%, 4%, and 6% (by weight binder). The stability and voids properties of asphalt mixture were determined based on Marshall Mix design test. Test results show that the stability of hot mix asphalt incorporating BRHA was higher than the controlled mixture. The results also indicate that the addition of BRHA causes an increasing or decreasing in voids properties.